Huang Qin Hua Shi decoction for high-temperature- and high-humidity-induced cognitive-behavioral disorder in rats is associated with deactivation of the hypothalamic–pituitary–adrenal axis. Issue 11 (November 2019) - Luo, Yong; Yang, Min; Guo, Mingyang; Zhong, Xiaolong; Hu, Yonghe
Objective: To investigate the effects of Huang Qin Hua Shi (HQ) decoction on the hypothalamic–pituitary–adrenal (HPA) axis in rats under high-temperature (hT)- and high-humidity (hH)-induced stress. Methods: Male rats were randomized into four groups: rats without stress; rats induced with hT (35 ± 1°C) and hH (85 ± 5% humidity); rats induced with hT and hH and treated with HQ decoction; and rats induced with hT and hH and treated with mifepristone. After 3 weeks, rats underwent the Morris water maze and open-field test. Rat hypothalami were analyzed pathologically using hematoxylin and eosin staining and glucocorticoid receptor (GR) mRNA expression was evaluated by in situ hybridization. Serum levels of corticotropin-releasing hormone (CRH), adrenocorticotropic hormone (ACTH), and corticosteroid (CORT) were assessed by enzyme-linked immunosorbent assay. Results: The administration of mifepristone or HQ in stressed rats significantly improved their performance in the Morris water maze test and increased the central-to-peripheral ratio and incidence of deep rearing in the open-field test. Mifepristone and HQ also reversed histological changes in the hypothalami of stressed rats. Compared with control rats, GR mRNA expression in the hypothalamus and serum CRH, ACTH, and CORT were significantly elevated in rats stressed with hT and hH, and these changes were attenuated by mifepristone and HQ. Conclusion: HQ decoction protects against hT- and hH-induced cognitive-behavioral disorder and its therapeutic effect is associated with decreased HPA axis activity.